Investigating the Implications of CFTR Exon Skipping Using a Cftr Exon 9 Deleted Mouse Model - Martinovich, Kelly M.; Kicic, Anthony; Stick, Stephen M.; Johnsen, Russell D.; Fletcher, Sue; Wilton, Steve D. (Frontiers in Pharmacology, 2022)
Introduction:Severity and disease progression in people with Cystic Fibrosis (CF) is typically dependent on their genotype. One potential therapeutic strategy for people with specific mutations exon skipping with antisense oligonucleotides(AO). The CFTR exon 9 is an in-frame exon therefor the exclusion of this exon would excise only 31 amino acids but not alter the reading frame of the remaining mRNA. This could be beneficial for people with class I mutations that affect exon 9 such as p.Trp401X. While the impact of exon 9 skipping on gene expression and cellular pathways can be studied in cells in vitro, trace amount of full-length normal or mutated material could cofound the testing. To overcome this limitation, the impact of CFTR exon 9 skipping on disease phenotype and severity is more effectively evaluated in a small animal model. This strategy is dependent on creating a milder CF phenotype relative to that associated with the original mutation. It was hypothesised that antisense oligonucleotide-mediated skipping this particular exon could result in a “mild mouse CF phenotype”. Methods:Cftr exon 9 deleted mice were generated using homologous recombination. Survival of homozygous (Cftr9/9) and heterozygous (Cftr9/) mice was compared to that of other CF mouse models, and lung and intestinal organ histology examined for any pathologies. Primary airway epithelial cells (pAECs) were harvested from Cftr9/9 mice and cultured at the Air Liquid Interface for CFTR functional assessment using Ussing Chamber analysis. Results:A Cftr9/9 mouse model presented with intestinal obstructions, and at time of weaning (21 days). Cftr9/9 mice had a survival rate of 83% that dropped to 38% by day 50. Histological sections of small intestine from Cftr9/9 mice showed more goblet cells and mucus accumulation that samples from the Cftr9/+ littermates. Airway epithelial cell cultures established from Cftr9/9 mice were not responsive to forskolin stimulation. Summary:The effect of Cftr exon 9 deletion on Cftr function was assessed and it was determined that the encoded Cftr isoform did not result in a milder “mouse CF disease phenotype,” suggesting that Cftr exon 9 is not dispensable, although further investigation in human CF pAECs would be required to confirm this observation.